2020
DOI: 10.3390/ma13132975
|View full text |Cite
|
Sign up to set email alerts
|

An Electrically Rechargeable Zinc/Air Cell with an Aqueous Choline Acetate Electrolyte

Abstract: Due to the feasibility of an electrically rechargeable zinc/air cell made of a zinc foil as active material, an aqueous choline acetate (ChAcO) mixture as an electrolyte and a spinel MnCo2O4 (MCO) and NiCo2O4 (NCO) as a bi-functional oxygen catalyst was investigated in this work. The 30 wt.% water-containing aqueous ChAcO solution showed high contact angles close to those of KOH favoring triple-phase boundary formation in the gas diffusion electrode. Conductivity and pH value of 30 wt.% H2O/ChAcO amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The electrochemical performance of choline‐based electrolytes has been recently assessed by Liu, Sakthivel et al . in Zn‐air cells [50–52] . It was found that aqueous choline acetate showed good compatibility with the selected electrode/catalyst and reduction of dendrite formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical performance of choline‐based electrolytes has been recently assessed by Liu, Sakthivel et al . in Zn‐air cells [50–52] . It was found that aqueous choline acetate showed good compatibility with the selected electrode/catalyst and reduction of dendrite formation.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical performance of choline-based electrolytes has been recently assessed by Liu, Sakthivel et al in Zn-air cells. [50][51][52] It was found that aqueous choline acetate showed good compatibility with the selected electrode/catalyst and reduction of dendrite formation. It has previously been shown that choline-based ILs exhibit a solvent-shared ion pair (SIP) configuration at high salt concentrations in the presence of H 2 O.…”
Section: Introductionmentioning
confidence: 99%